A two‐phase approach to identifying HFpEF in heart failure patients: Risk score evaluation and decision tree development - Izabella Uchmanowicz; Magdalena Lisiak; Piotr Ponikowski; Ewa A. Jankowska; Andrzej Mysiak; Marta Wleklik (ESC Heart Failure)
Abstract Aims Heart failure (HF) with preserved ejection fraction (HFpEF) poses significant diagnostic challenges due to its complex aetiology and overlapping symptoms with other HF types. The heterogeneity of HFpEF, compounded by frequent comorbidities, complicates diagnosis. This study aimed to enhance HFpEF prediction through a two‐phase approach: a simplified risk score and a decision tree model. Methods and results In Phase 1, an 8‐point risk score based on accessible clinical parameters was developed. In Phase 2, we conducted comprehensive predictive modelling using decision tree analysis. Data from 560 HF patients were analysed. It achieved an accuracy of 63.13% (sensitivity: 62.87%, specificity: 54.24%). In Phase 2, a decision tree model using broader clinical variables improved accuracy to 73.04% (sensitivity: 53.89%, specificity: 81.17%). Conclusions This dual framework provides tools for both quick screening and detailed risk stratification in various clinical settings.